Answer:
To solve this equation, we need to use the order of operations, which is PEMDAS (Parentheses, Exponents, Multiplication and Division, Addition and Subtraction).
First, we need to simplify the expression inside the parentheses:
6 - 3/3(7x + 2) = 6(8 - 3)
6 - 1(7x + 2) = 6(5)
6 - 7x - 2 = 30
4 - 7x = 30
Next, we need to isolate the variable (x) on one side of the equation. We can do this by subtracting 4 from both sides:
4 - 7x - 4 = 30 - 4
-7x = 26
Finally, we can solve for x by dividing both sides by -7:
x = -26/7
Therefore, the solution to the equation is x = -26/7.